2014
DOI: 10.1002/pssr.201409013
|View full text |Cite
|
Sign up to set email alerts
|

Ab‐initio calculations and structural studies of (SiTe)2(Sb2Te3)n (n: 1, 2, 4 and 6) phase‐change superlattice films

Abstract: (SiTe)2(Sb2Te3)n phase‐change superlattices were investigated theoretically and experimentally. Ab‐initio first principle simulations predicted that the (SiTe)2(Sb2Te3)n structures are stable and possess a Dirac semimetal‐like band structure. Calculation of the Z2 invariant indicated that the structure was topologically nontrivial. (SiTe)2(Sb2Te3)n superlattice structures derived from first‐principles were successfully fabricated on a Si substrate by RF‐magnetron sputtering. XRD and TEM indicated that the supe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 19 publications
0
21
0
Order By: Relevance
“…For one sample, a chalcogenide film was deposited directly onto the substrate (iii), while for another piece of the same sample, surface sputtering using Ar was carried out prior to film deposition ((iv) and (v)). It should be noted that not only was an Sb2Te3 single film deposited but also GeTe/Sb2Te3 and SiTe/Sb2Te3 superlattice films were fabricated in order to test the application of this method for the fabrication of PCRAM . In all cases, an Sb2Te3 film was initially deposited to allow for the growth of highly oriented GeTe or SiTe compounds ().…”
Section: Experimental Methodsmentioning
confidence: 99%
“…For one sample, a chalcogenide film was deposited directly onto the substrate (iii), while for another piece of the same sample, surface sputtering using Ar was carried out prior to film deposition ((iv) and (v)). It should be noted that not only was an Sb2Te3 single film deposited but also GeTe/Sb2Te3 and SiTe/Sb2Te3 superlattice films were fabricated in order to test the application of this method for the fabrication of PCRAM . In all cases, an Sb2Te3 film was initially deposited to allow for the growth of highly oriented GeTe or SiTe compounds ().…”
Section: Experimental Methodsmentioning
confidence: 99%
“…Liu et al reported a multilayer [(SnSb 4 ) 30 nm /(SbSe) 20 nm ] 1 film that possessed fast switching speed (<5 ns) and good thermal stability (ten‐year‐retention temperature = 122 °C) . Saito et al also predicted that the [(SiTe) 2 /(Sb 2 Te 3 ) y ] superlattice may be a possible phase change materials . To summarize, the advantages of superlattice or superlattice‐like phase change materials do not exclusively rely on the composition of [(GeTe) x /(Sb 2 Te 3 ) y ] n .…”
Section: Optimization Of Superlattice For Advanced Performancementioning
confidence: 99%
“…52 Some attempts to replace Ge by different elements have also been reported; tuning the composition has an even greater possibility of further improving iPCM performance. 53,54 In conclusion, we have explored the structural dynamics and electronic structural changes in We also note that the presence of both Ge and Sb atoms on cation planes adjacent to vdW gaps, i.e. Ge/Sb intermixing, is crucial for the iPCM switching.…”
mentioning
confidence: 94%